A case of autophagia with thalamic hemorrhage. (July 2022) - Sidow, Nor Osman; Sheikh Hassan, Mohamed
Abstract: Autophagia occurs when one is compelled to inflict pain upon oneself by biting and/or devouring portions of one's body. It is sometimes associated with psychiatric disorders or with acquired nervous system lesions and could be life-threatening (The Journal of Nervous and Mental Disease, February 2012) [2]. It is the first time that this behavior was seen in post-stroke patients, not reported in the medical literature before. A 65-years-old male patient was seen in our emergency department with left side weakness, and agitation that he had self-mutilated his index finger as the same time for one day before admission. He has no previous history of psychiatric illnesses, only he had hypertension. Head CT showed hematoma in the right thalamic and basal ganglia, after orthopedic consultation, the terminal phalange of the index finger in the left hand was amputated, and antipsychotic drugs was started with significant recovery. So thalamic hemorrhage can cause agitation and self mutilating behavior. Autophagia could be classified under the DSM's Impulse-Control Disorders.Self-mutilation is a severe form of self-injury. Both involve a deliberate and direct injury to one's own body surface without suicidal intent (Claes and Vandereycken, 2007) (Resch et al., 2008) [5].